Anish Kapoor : dirty corner - Kapoor, Anish; Mercurio, Gianni; Paparoni, Demetrio; Fabbrica del Vapore (Milan, Italy); Rotonda di via Besana (Milano : Skira ; New York : Rizzoli International [Distributor], 2011)
Comprising of sketchbook drawings, paintings, architectural models, and sculpture dating from 1974 to the present day, DIRTY CORNER focuses on the consistent concert in Anish Kapoor's work with the void: as vertiginous fall, as wound and as origin. Featuring previously unpublished material, this volume reveals the integral contiguity of these issues in Kapoor's work and offers an invaluable insight into the artist's practise.--fascia.
Catalog of an exhibition held at Rotonda di via Besana, Milan, 31 May-9 October, 2011, and Fabbrica del Vapore, Milan, 31 May 2011 to 8 January 2012.
Includes bibliographical references.
boek
Keywords: Kapoor, Anish, -- Exhibitions